The Use of Adenovirus Dodecahedron in the Delivery of an Enzymatic Activity in the Cell. (8th May 2016) - Sumarheni; Gallet, Benoit; Fender, Pascal
Abstract : Penton-dodecahedron (Pt-Dd) derived from adenovirus type 3 is a symmetric complex of pentameric penton base plus fiber which can be produced in the baculovirus system at a high concentration. The size of Pt-Dd is smaller than the virus, but this virus-like particle (VLP) has the major proteins recognized by specific receptors on the surface of almost all types of cell. In this study, by direct observation with fluorescence microscopy on a fixed and living cell, the intracellular trafficking and localization of Pt-Dd labeled with fluorescence dyes in the cytoplasm of HeLa Tub-GFP showed a rapid internalization characteristic. Subsequently, the linkage of horseradish peroxidase (HRP) with Pt-Dd as the vector demonstrated an efficient system to deliver this enzyme into the cell without interfering its enzymatic activity as shown by biochemical and cellular experiments. These results were supported by additional studies using Bs-Dd or free form of the HRP used as the control. Overall, this study strengthens the potential role of Pt-Dd as an alternative vector for delivering therapeutic agents.